Integrated Weed Management (IWM) in Rice in Côte d'Ivoire - CGIAR Research Program on Rice (2019)
On-station testing of IWM practices in Mbe, Bouake in on-going. Demonstration of weeders and participatory evaluation of herbicide molecules has been conducted in Bouake and Gagnoa regions in wet season 2019.